The Drosophila homeodomain transcription factor Homeobrain is involved in the formation of the embryonic protocerebrum and the supraesophageal brain commissure - Kolb, Dieter; Kaspar, Petra; Klöppel, Christine; Walldorf, Uwe (Cells & development, 2021)
During the embryonic development of Drosophila melanogaster many transcriptional activators are involved in the formation of the embryonic brain. In our study we show that the transcription factor Homeobrain (Hbn), a member of the 57B homeobox gene cluster, is an additional factor involved in the formation of the embryonic Drosophila brain. Using a Hbn antibody and specific cell type markers a detailed expression analysis during embryonic brain development was conducted. We show that Hbn is expressed in several regions in the protocerebrum, including fibre tract founder cells closely associated with the supraesophageal brain commissure and also in the mushroom bodies. During the formation of the supraesophageal commissure, Hbn and FasII-positive founder cells build an interhemispheric bridge priming the commissure and thereby linking both brain hemispheres. The Hbn expression is restricted to neural but not glial cells in the embryonic brain. In a mutagenesis screen we generated two mutant hbn alleles that both show embryonic lethality. The phenotype of the hbn mutant alleles is characterized by a reduction of the protocerebrum, a loss of the supraesophageal commissure and mushroom body progenitors and also by a dislocation of the optic lobes. Extensive apoptosis correlates with the impaired formation of the embryonic protocerebrum and the supraesophageal commissure. Our results show that Hbn is another important factor for embryonic brain development in Drosophila melanogaster.
Online veröffentlicht am 8. Februar 2021
Gesehen am 01.10.2021